Impact of Quality Product and Quality Service of Ayam Merangkat Culinary Tourism Services on the Satisfaction and Loyalty of Tourists Who Visit Lesehan Bamboo Market, Bonjeruk Tourism Village, Central Lombok - Meitisrilatifatulain Fitriadewi Mariana; I Nyoman Sudiarta; I Wayan Suardana (International journal of technology and education research, 2024)
Bonjeruk Tourism Village is a tourist village that has popular culinary tourism in Lombok, specifically in Lesehan Ayam Merangkat, Bonjeruk Bamboo Market Tourism Village, and Central Lombok Regency, which is a place to sell various Lombok culinary specialties, and one of them is Ayam Merangkat, which is a superior product of Bonjeruk Tourism Village.The data collection technique in this study uses a questionnaire, and then the sample determination technique uses acendental sampling, which is the determination of respondents based on who was in the field at the time of the research. In this study, the sample in question is tourists who have visited Lesehan Ayam Merangkat Bamboo Market, Bonjeruk Tourism Village, at least twice. The data analysis technique used in this research is quantitative descriptive, followed by hypothesis testing using smart PLS software. The result of this study is to conclude that, based on the t-test, the t-statistical value used as a measure of the significance of the influence each variable must be higher than 1.96. Based on this, the results obtained in this study are that the quality of culinary tourism products (X1) has a significant effect on satisfaction (Y1), service quality (X2) has a significant effect on satisfaction (Y1), the quality of culinary tourism products (X1) does not have a significant influence on loyalty (Y2), service quality (X1) does not have a significant influence on loyalty (Y2), and satisfaction (Y1) has a significant influence on loyalty (Y2).